Curso de Inteligência Artificial para Idosos - Inclusão Digital e Bem-Estar em Saúde - Lira, Caroline Barbosa de Oliveira; Rodrigues, Kamila Rios da Hora (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This extension activity presents a short course designed for older adults (60+), aimed at promoting digital literacy and understanding of artificial intelligence (AI). The course structure is based on a four-axis framework — educational, technological, ethical-legal, and socio-emotional — and was designed from the demands and interests of the participants, placing them at the center of the learning process. With a total of four hours divided into five interactive modules, the course combines brief lectures, guided practical activities, and collective reflection. Preliminary indicators, such as high demand and participant inquiries, demonstrate strong societal interest and the relevance of the initiative. This activity seeks to fill a significant gap in digital education for older adults, fostering autonomy, confidence, and critical awareness regarding the use of technology and AI in everyday life.